EFFECTS OF MARKETING PROCESSES ON SMALL SCALE COFFEE PRODUCTION IN KANGUNDO SUB-COUNTY, MACHAKOS COUNTY, KENYA - Kaula, Francis Mutethya; Arasa, Robert; Nzioki, Susan (International Journal of Economics, Commerce and Management, 2019)
Coffee production in Kenya has continued to suffer negative growth since 1989 with severe consequences to the coffee economy which is a source of foreign exchange to the country, farm incomes and employment. While coffee production continues to decline in Kenya, production in most of the other coffee growing countries continues to grow. This study adopted descriptive survey design and was carried out with an aim of exposing the influence of marketing processes on Primary source included use of questionnaires. The target population was 11,348 smallholder coffee farmers who are spread in 6 coffee cooperative societies in Kangundo Subcounty. The study surveyed all the 6 societies in Kangundo Sub-county. Two factors were sampled through simple random technique. The study employed Krejcie and Morgan (1970) sample size table to determine the appropriate sample of coffee farmers to be included in the study. Out of 11,348 farmers, the study included 370 small-scale farmers who were randomly selected. A validated and vetted questionnaire was administered to selected farmers throughthe help of a translator. Data analysis was both qualitative and quantitative using descriptive statistics. The study findings show that there are several marketing factors that discourage farmers from coffee farming such as poor management of coffee societies, societies’ debts, non-provision of timely marketing information, presence of middlemen and delays in coffee payment after the auction. To revitalize the declining coffee industry, this paper recommends to the government of Kenya to consider amending the Crops Act (2013) to allow for different marketing channels on top of the cooperative system.
Keywords: Small scale, Coffee Production, Marketing Processes, Cooperative Societies, Smallholder Farmer